Representation of aerosol optical properties using a chemistry transport model to improve solar irradiance modelling. (December 2018) - Sartelet, Karine; Legorgeu, Carole; Lugon, Lya; Maanane, Yassine; Musson-Genon, Luc
Highlights: Accurate aerosol optical properties modelling improves modelled clear-sky radiation. Amongst aerosol optical properties (AOP), the most important is optical depth. AOP at 6 wavelengths are enough to integrate AOP over the radiation wavelengths. Abstract: Atmospheric particles may attenuate solar irradiance effectively during clear-sky days, but attenuation by particles is sometimes not taken into account in numerical models, or it is often parameterised using constant or climatological values for example. This paper compares different representations of the effects of particles on direct and global solar irradiance, using the software Code_Saturne. Particle concentrations, as well as aerosol optical properties AOPs (optical thickness, asymmetry factor and single scattering albedo), are estimated using the air-quality modelling platform Polyphemus. Modelled solar irradiance is compared to measurements in greater Paris and the south of France. Accurate modelling of AOPs leads to an improvement of statistical error indicators, especially in clear-sky conditions. A simplified scheme represents AOPs integrated over the full spectral range using only 6 wavelengths, and a sensitivity study on the influence of assumptions in AOPs on solar irradiance is performed.